A simplified heat transfer model of a closed refrigerated display cabinet. - Nattawut Chaomuang; Onrawee Laguerre; D. Flick (HAL (Le Centre pour la Communication Scientifique Directe), 2021)
International audience
Keywords: Food Supply Chain Traceability; Food Safety and Hygiene; Meat and Animal Product Quality